2009
DOI: 10.1002/mrd.21045
|View full text |Cite
|
Sign up to set email alerts
|

Use of picosecond infrared laser for micromanipulation of early mammalian embryos

Abstract: A high repetition rate (80 MHz) picosecond pulse (approximately 2 psec) infrared laser was used for the inactivation (functional enucleation) of oocytes and two-cell mouse embryos and also for the fusion of blastomeres of two-cell mouse embryos. The laser inactivation of both blastomeres of two-cell mouse embryos by irradiation of nucleoli completely blocked further development of the embryo. The inactivation of one blastomere, however, did not affect the ability of the second intact blastomere to develop into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Corresponding data were already published for Drosophila and zebrafish embryos [1]. First results about functional enucleation of mammalian oocytes by laser irradiation of the metaphase plate were obtained in our experiments in mice [2] and repeated later on in pigs [3]. Furthermore, we showed that is possible to perform the entire mammalian cloning procedure at all stages of nuclear transplantation only with the use of laser [4].…”
Section: Introductionsupporting
confidence: 78%
“…Corresponding data were already published for Drosophila and zebrafish embryos [1]. First results about functional enucleation of mammalian oocytes by laser irradiation of the metaphase plate were obtained in our experiments in mice [2] and repeated later on in pigs [3]. Furthermore, we showed that is possible to perform the entire mammalian cloning procedure at all stages of nuclear transplantation only with the use of laser [4].…”
Section: Introductionsupporting
confidence: 78%
“…In earlier papers it has been shown that nanosecond lasers may be successfully applied for embryo microsurgery [12,13]. At the present time picosecond [14] and femtosecond (fs) lasers [15][16][17] are mainly used. It should be pointed out that femtosecond lasers have several advantages as compared to continuous wave (CW) lasers or long-pulsed lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, laser irradiation had no apparent detrimental effects on the cytoplasm and nuclear DNA, both involved in cell division, which is in very good agreement with previous fusion experiments. 8 A ploidy analysis of embryos developed to the blastocyst stage revealed that tetraploid cells were present in some fused embryos at this stage (data not shown). This indicates that nuclear fusion may occur within a few hours after laser treatment [see Fig.…”
Section: Discussionmentioning
confidence: 95%
“…For parthenogenetic twocell stage embryos, we achieved a fusion efficiency of 55% with porcine cells which is comparable to previous experiments with mouse cells (65%). 8 Long-term viability of fused two-cell porcine embryos was demonstrated by successful development up to the blastocyst stage with no significant difference to controls [see Fig. 6(a)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation